Chapter 11 Photoacoustics - A Novel Tool for the Study of Aquatic Photosynthesis - Pinchasov-Grinblat, Yulia (InTechOpen, 2013)
The photoacoustic method allows direct determination of the energy-storage efficiency of photosynthesis by relating the energy stored by it to the total light energy absorbed by the plant material (Canaani et al., 1988; Malkin & Cahen, 1979; Malkin et al., 1990). These authors applied the photoacoustic method to leaves in the gas phase, where brief pulses caused concomitant pulses of oxygen that caused a pressure transient detected by a microphone. This method is based on the conversion of absorbed light to heat. Depending on the efficiency of the photosynthetic system, a variable fraction of the absorbed light energy is stored, thereby affecting the heat evolved and the resulting photoacoustic signal. The higher the photosynthetic efficiency, the greater will be the difference between the stored energy with and without ongoing photosynthesis (Cha & Mauzerall, 1992). These authors collected microalgal cells onto a filter and studied them by an approach similar to that previously used with leaves. In both cases, the oxygen signal is combined with that of thermal expansion resulting from conversion of the fraction of the light energy in the pulse that is not stored by photochemistry.